ANALISIS TEKNIK DAN TAKTIK DALAM BERTANDING ATLET PENCAK SILAT CLUB BINAAN PRESTASI CIREBON TIMUR UNTUK MENINGKATKAN KUALITAS BERTANDING ATLET - Teguh Bilal Nurhadian Billah; Dani Nurdiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ANALISIS TEKNIK DAN TAKTIK DALAM BERTANDING ATLET PENCAK SILAT CLUBBINAAN PRESTASI CIREBON TIMUR UNTUK MENINGKATKAN KUALITASBERTANDING ATLET. Sports play an important role not only in maintaining physical andmental health, but also as a means of achieving performance. One of the martial arts thatemphasizes technical and tactical aspects in competition is Pencak Silat. This study aims toanalyze the techniques and tactics used by athletes of the Pencak Silat Club Binaan PrestasiCirebon Timur in order to improve competition quality. The research method employed wasobservation/survey with a quantitative approach. The results show that in the technicalaspect of male athletes, the highest percentage was found in the throwing category with36%, followed by kicking with the highest percentage of 36% and punching with the highestpercentage of 26%. Meanwhile, in the tactical aspect of female athletes, the highestpercentage was in the attacking category with 60%, followed by defending with 51% andwith 50%.